Chaotic Image Encryption: State-of-the-Art, Ecosystem, and Future Roadmap - Zolfaghari, Behrouz; Koshiba, Takeshi (Applied System Innovation, 2022)
Recently, many researchers have been interested in the application of chaos in cryptography. Specifically, numerous research works have been focusing on chaotic image encryption. A comprehensive survey can highlight existing trends and shed light on less-studied topics in the area of chaotic image encryption. In addition to such a survey, this paper studies the main challenges in this field, establishes an ecosystem for chaotic image encryption, and develops a future roadmap for further research in this area.